The problem of merge - Destéfano, Mariela Natalia (2020)
Focusing on biolinguistic considerations, Merge is a formal operation proposed by theoretical linguistics and linked to specific principles of neural computation. In this sense, Merge can be viewed as a natural operation of the brain. Merge is commonly claimed to be a digital operation. In a first approximation, digital computation is the processing of strings of digits according to general rules defined over these digits. However, it seems that neural processes are not digital computations. These conflictive claims, e.g. the digital characterization of Merge and the non-digital characterization of the brain, leads to the following scenario: either Merge is an operation that is not realized in the brain or Merge is realized in the brain but not digitally. The purpose of this paper is to evaluate the problems posed by each thesis.